Potensi Destinasi Wisata dalam Pengembangan Wilayah di Kota Tanjungbalai - Fiqrida Amalia; Ahmad Rivai (JURNAL EKUIVALENSI, 2022)
This study aims to describe the potential of tourist destinations in regional development in Tanjungbalai City. This research uses qualitative research with descriptive method. The research findings show that tourist destinations in Tanjungbalai City play an important role in regional development in Tanjungbalai City. The role of tourist destinations in this city is also supported by the availability of adequate accommodation and accessibility facilities. The existence of various tourist objects and destinations in Tanjungbalai City also has a socio-economic impact for the community around the tourist attraction locations and helps reduce unemployment in Tanjungbalai City.